Analysis of Reverse Osmosis Separation Performances of Ethanol/Water Mixtures and Design of Ethanol Concentration Processes - Kazuki Akamatsu; Tomonori Kimura; Shigeo Oba; Shin-ichi Nakao (Journal of Chemical Engineering of Japan)
This study successfully analyzed the reverse osmosis (RO) separation performances of ethanol/water mixture (1–37 wt% of ethanol) with polymeric RO membranes using transport equations derived on the basis of the solution-diffusion mechanism in which the permeation flux is proportional to the chemical potential gradient. It was demonstrated that the obtained permeation data were well correlated with the transport equations. By utilizing the analyzed results, multi-stage RO processes for ethanol concentration from 5 to 40 wt% were evaluated in terms of required energy with the conventional distillation design. According to the process evaluation, existing polymeric RO membranes for desalination were not applicable to the ethanol concentration since estimated required energy was larger than distillation. Instead, RO membrane having assumed hypothetical permeance values for ethanol of 0.1 times and water of 2 times was proved to be feasible to achieve lower energy consumption, which can be used as a design guide.